CORRECTION OF TONGUE THRUSTING HABIT –A CASE REPORT - Brightlin Angela R; Ponnudurai Arangannal; Jeevarathan; JananiVinodhini; Madhumitha; IshwaryaDhevi G R (The Bioscan, 2025)
Anterior open bite, contributing cause of tongue thrusting and the management of such habits requires the removal of the underlying etiology, retraining exercises andorthodontic appliances. The most commonly used appliance for habit breaking especially tongue thrusting is by using palatal crib or palatal spurs.The persistence of such habits can affect the development of orofacial complex resulting in complex dental problems in adulthood.This clinical case report deals with the therapeutic management of tongue thrusting habit in an 8- year-old child. The interceptive modality employed was fixed palatal crib appliance for duration of five months.